American Slaughterhouses and the Need for Speed: An Examination of the Meatpacking-Methamphetamine Hypothesis. (June 2018) - Hendrix, Joshua A.; Dollar, Cindy Brooks
In Fast Food Nation, Eric Schlosser argues that slaughterhouse workers use methamphetamines to manage the harsh physical and emotional demands of the meatpacking industry. Similar ideas have been raised elsewhere; however, empirical tests of this hypothesis are in short supply. In this article, we elaborate on theoretical mechanisms that may explain why the meatpacking industry encourages methamphetamine use and provide a macro-level test of the meatpacking–methamphetamine hypothesis using 11 years (2001-2012) of hospital admission data and information from annual livestock slaughter reports. Decomposition modeling is used to examine variations across states and within states over time. Results show only modest support for the hypothesis. Specifically, a combined measure of meat is positively and statistically significantly associated with methamphetamine use both within and across states. However, the relationships are not consistently positive or statistically significant across all types of meat. In other words, the meatpacking–methamphetamine relationship is varying and complex.